Smart Attendance System for Covid-19 Social Distancing - Arshad, Nur Amalina (Progress in Engineering Application and Technology, 2022)
The purpose of this project is to develop a GUI-based system that can record student attendance using a QR Code during the Covid19 pandemic. When lecturers use paper as a record of the student attendance, students do not follow social distancing that causes several direct contacts. The objective of this study is to design a Smart Attendance System using QR code by developing a Graphical User Interface (GUI) that will be integrated with the QR code system and develop a database. The system is also able to record student temperatures when attendance is recorded. The development process of the Smart Attendance System is based on the design, development of the ADDIE model which contains five phases, namely analysis, design, development, implementation, and evaluation. Visual Basic is used to produce interface displays and databases are developed using Microsoft Access. Altogether, the designed system is capable of helping lecturers to take student attendance faster and easier. While, avoiding close contact among students.